2018
DOI: 10.18203/2394-6040.ijcmph20180274
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-medication practices among the residents of urban slums located near govt. medical college, Jabalpur

Abstract: Background: Self-medication is defined as medication taken on the patient’s own initiative or on the advice of pharmacist or any other lay person. Self-medication can be described as a double edged sword for its users, because it has both beneficial and harmful effects. According to recent community based study in 2016 prevalence of self-medication in developing countries varies from 12% to as high as 73% in different communities. The objectives of the study were to assess the prevalence of self-medication amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(24 reference statements)
1
3
2
Order By: Relevance
“…This disparity could be explained by the fact that during the COVID-19 lockdown, the public was not moving freely, making it difficult for them to obtain drugs. The prevalence of self-medication in our study, however, was way higher than that reported among residents of urban slums [32]. This discrepancy can be explained by the fact that both of these studies were conducted way before the COVID-19 pandemic which started almost three years later.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This disparity could be explained by the fact that during the COVID-19 lockdown, the public was not moving freely, making it difficult for them to obtain drugs. The prevalence of self-medication in our study, however, was way higher than that reported among residents of urban slums [32]. This discrepancy can be explained by the fact that both of these studies were conducted way before the COVID-19 pandemic which started almost three years later.…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, studies conducted in Uganda, Eritrea, Ethiopia, Nigeria, Belgrade and Cameroon have reported that as one gets older, they acquire accumulated knowledge due to disease experience [33][34][35][36][37][38][39][40]. Contrary studies have been done in Jabalpur [32] and Syrian [41], where individuals aged 18 to 40 years were more likely to self-medicate. This age difference could be due to the population dynamics of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the prevalence in our study was not that alarming. In concordance with studies done by Jain et. al.…”
Section: Discussionsupporting
confidence: 93%
“…12 Similarly, in another study, major factors leading to selfmedication were simple disease (56.50%), easy availability of drugs (50.80%), self-decision (31.40%), and timesaving (28.00%). 13 In this present study, it was concluded that there was no association between socio-demographic variables and the prevalence of self-medication except association seen with gender. On the contrary, a study which was conducted among 2000 university students of Southwestern Nigeria revealed that there was a significant association between the prevalence of self-medication and age, gender, and educational status.…”
Section: Discussioncontrasting
confidence: 50%